Analisis Wacana Sara Mills Pada Berita Pemerkosaan Anak Di Bawah Umur Studi pada Berita Harian Kompas.Com - Muawanah, Lutfi (Universitas Islam Negeri Raden Intan Lampung, 2021)
Mass media is very influential in people's lives. Mass media serves to provide information to the audience. Underage rapes are still common and appear in news in print and electronic media. Although there are already laws that govern, but do not scare the perpetrators. There's even an abuser who tortures his victim and kills her. Media kompas.com always preach about the phenomenon that is happening in people's lives. The method in this study uses descriptive qualitative research method by providing a description by studying the content of text contained in the news in the form of words. The analysis was conducted with a critical discourse analysis approach using Sara Mills' theory on news texts reported on online media Kompas.com. The results of this study put women as objects in the text, because on the news of underage women are always victims of rape who get inappropriate treatment and lead to death. In this case, the media Kompas.com show women being victims of rape told in texts that someone has subjected. But in the media Kompas.com also put the position of women as subjects who have the opportunity to tell the events they experienced. Through this news, the author makes the reader, especially the male, aware not to commit the abuse.